ANALISIS PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PENGUNJUNG PADA WISATA BAHARI LAMONGAN - Candra Setiawan; Sunar yo (Jurnal Ilmiah Mahasiswa FEB, 2013)
Indonesia is an archipelago scattered extends from the western end of Sabang until Merauke East end so very profitable tourism industry. The current tourism industry has become the object of hope big enough  foreign exchange earner for the country. To enhance the tourism industry in Indonesia, the Government is trying to improve and develop all aspects that can arouse desire domestic and foreign tourist places to visit in Indonesia. This research was meant to  find out the influence of the dimensions of the quality of being composed of tangible, empathy, responsiveness, reliability and assurance against customer satisfaction both simultaneously or partial and to know and analyzing the independent variable which  is influential most dominant to customer satisfaction. The study is done use the device linear regression analysis worship of idols with a sample of visitors on a visit to tourism lamongan and has a visit as many as one times as many as 150 respondents. This type of research is explanatory research conducted with survey methods. Using a purposive sampling technique of sampling. Data sources used are primary data are secondary data and questionnaire results which the company archives and literature.  Multiple linear regression analysis of the results of this research are tangible variables, empathy, responsiveness, reliability and assurance influential simultaneously towards customer satisfaction. In addition, tangible variable empathy, responsiveness, reliability and assurance are also influential in partial towards customer satisfaction. In this study can be known also that tangible variables significantly influential dominant towards customer satisfaction.Keyword :  tangible, empathy, responsiveness, reliability, assurance and customer satisfaction